Three dimensional simulation of seawater intrusion in coastal aquifers: A case study in the Goksu Deltaic Plain - Cobaner, Murat; Yurtal, Recep; Dogan, Ahmet; Motz, Louis H. (ELSEVIER SCIENCE BV, 2012)
Unplanned exploitation of groundwater from coastal aquifers may cause salt water intrusion in coastal aquifers. Coastal areas are generally overpopulated with fertile agricultural lands and diversified irrigated farming activities. The objective of this study was to develop a model to control/prevent seawater intrusion into the coastal aquifer with a case study of the Silifke-Goksu Deltaic Plain. A computer program for the simulation of three-dimensional variable density groundwater flow, SEAWAT, is used to model the seawater intrusion mechanism of the Goksu Deltaic Plain along the Mediterranean coast of Turkey. The calibration analysis of the developed seawater intrusion model is performed using field measured data in the water-year of 2008 including static groundwater head, electrical conductivity, total dissolved solid (TDS), and chloride concentration values collected from 23 observation wells and the existing data which were compiled and reviewed. The main objectives for applying the seawater intrusion model to the Goksu Deltaic Plain were (1) to determine the hydraulic and hydrogeologic parameters of the aquifer, (2) to estimate the spatial variation of the salt concentration in the aquifer and (3) to investigate the impact of the increase and decrease in groundwater extractions. The simulation results show that the Goksu Deltaic Plain aquifer is especially sensitive to the increase in groundwater extraction. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Groundwater modeling; Seawater intrusion; Goksu Deltaic Plain; SEAWAT; WATER INTERFACE MOTION; FRESH-WATER; SALTWATER INTRUSION; SALT-WATER; FLOW; SURFACE; FLORIDA; MODEL; QUEENSLAND; MANAGEMENT; Engineering; Geology; Water Resources